Gerakan Oikumene di Indonesia dan Tantangan Lintas Agama - Tupa Pebrianti Lumbantoruan; Meditatio Situmorang (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The ecumenical movement in Indonesia was born as a response to the biblical call to realize the unity of Christians, especially in the context of cultural, ethnic and religious diversity. As a country with high plurality, Indonesia is a fertile and challenging field for this movement. Oikumene, derived from the Greek word oikoumene, means “inhabited world”. In this context, the ecumenical movement aims to unite churches to witness the Gospel together in a complex and diverse world. However, the implementation of this movement is not free from various dynamics and challenges, especially in interfaith relations. One of the main challenges is the differences in theology, tradition and liturgy between churches, which become internal obstacles to realizing complete unity. Churches in Indonesia often face difficulties in reaching agreement on common issues, such as evangelism, social services, and approaches to interfaith dialog. On the other hand, external challenges arise from the dynamics of interfaith relations in Indonesia, which are often characterized by tensions, stereotypes, and even conflicts. Government policies related to religion, such as the regulation of houses of worship, also often put churches in a difficult position, thus affecting their efforts to unite.Nevertheless, the ecumenical movement in Indonesia still plays a significant role in promoting interfaith dialogue. By emphasizing the importance of cooperation on social issues, such as justice, peace and poverty alleviation, the movement is able to serve as a bridge between Christian communities and other religions. The role of organizations such as the Persekutuan Gereja-Gereja di Indonesia (PGI) is very important in realizing constructive dialogue. Through this approach, ecumenism is not only an internal effort of the church to unite, but also a contribution of Christians to interfaith harmony in Indonesia.keywords: The Oikumene Movement in Indonesia and interfaith challenges